2018
DOI: 10.1007/s12031-018-1056-8
|View full text |Cite
|
Sign up to set email alerts
|

Schwann-Cell Autophagy, Functional Recovery, and Scar Reduction After Peripheral Nerve Repair

Abstract: The functional outcome after peripheral nerve repair is often unpredictable for many reasons, e.g., the severity of neuronal death and scarring. Axonal degeneration significantly affects outcomes. Post-injury axonal degeneration in peripheral nerves is accompanied by myelin degradation initiated by Schwann cells (SCs), which activate autophagy, a ubiquitous cytoprotective process essential for degrading and recycling cellular constituents. Scar formation occurs concomitantly with nerve insult and axonal degene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Schwann cells, as a type of glial and myelin-forming cell, are widely used in in vitro studies of peripheral nervous system diseases (23). Previous studies have shown that injury of Schwann cells can cause peripheral nerve damage, including segmental demyelination (one of the characteristic changes of DPN), a reduction in nerve conduction velocity, acceleration of axonal atrophy and inhibition of nerve repair (24), which all result in the occurrence of DPN (25). As Schwann cells absorb glucose through an insulin-independent pathway, they are more sensitive to hyperglycemia and more susceptible to attack by HG (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schwann cells, as a type of glial and myelin-forming cell, are widely used in in vitro studies of peripheral nervous system diseases (23). Previous studies have shown that injury of Schwann cells can cause peripheral nerve damage, including segmental demyelination (one of the characteristic changes of DPN), a reduction in nerve conduction velocity, acceleration of axonal atrophy and inhibition of nerve repair (24), which all result in the occurrence of DPN (25). As Schwann cells absorb glucose through an insulin-independent pathway, they are more sensitive to hyperglycemia and more susceptible to attack by HG (26).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely recognized that hyperglycemia, which occurs in all patients with diabetes mellitus, is the main reason for diabetic complications (5). As damage to Schwann cells is reversible (24), Schwann cells may be a target in the treatment of DPN. Therefore, HG (50 mM) was used to treat RSCs for 48 h in order to induce an in vitro model of DPN in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…After trigeminal nerve injury, axons degenerate and demyelinate due to compression or inflammation 27 . Activated SCs destroy the myelin sheath and engulf axon fragments and the detached myelin sheath, which leads to TN 28,29 . Otherwise; activated SCs secrete molecules that induce hypersensitivity to pain, which leads to a decreased pain threshold that triggers TN 9,14 .…”
Section: Scs and Production Of Tnmentioning
confidence: 99%
“…27 Activated SCs destroy the myelin sheath and engulf axon fragments and the detached myelin sheath, which leads to TN. 28,29 Otherwise, activated SCs secrete molecules that induce hypersensitivity to pain, which leads to a decreased pain threshold that triggers TN. 9,14 Trigeminal nerve demyelination, which is considered an important cause of TN, is caused by trigeminal nerve injury; 30,31 meanwhile, neurons in the trigeminal semilunar ganglion are activated to form the ignition focus.…”
Section: Scs and Production Of Tnmentioning
confidence: 99%
“…Interestingly, inhibiting Schwann cell autophagy pharmacologically with 3-methyladenine or using a mouse haploinsufficient at the Ambra1 gene resulted in increased and prolonged neuropathic pain behavior after nerve injury (Marinelli et al, 2014). Furthermore, inhibition of autophagy after nerve damage is accompanied by increased neurofilament accumulation (Ko et al, 2018), suggesting that Schwann cell autophagy slows and ameliorates scar formation after injury.…”
Section: Schwann Cell Autophagy: Pharmacological Manipulation Of Myelmentioning
confidence: 99%